Implementation of Training in Improving Hospitality Services At Dr. R. Goeteng Taroenadibrata Purbalingga Hospital - Zahrotunnisa Arizky; Rian Andriani; R Oke Andikarya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the implementation of training programs in improving hospitality services at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The study is motivated by the need to enhance hospital service quality, which should not only focus on medical aspects but also on non-medical aspects such as friendliness, empathy, and effective communication with patients and their families. A qualitative descriptive approach was employed involving 13 informants consisting of hospital employees, health workers, and non-health staff. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that hospitality training has been conducted regularly, covering interpersonal communication, service excellence, and the development of patient-friendly attitudes. The implementation of the training has increased employees’ awareness of patient-oriented services. However, several challenges remain, including limited training duration, lecture-dominated learning methods, unequal training opportunities for all staff including outsourced workers, and limited post-training evaluation to measure behavioral changes. Therefore, this study recommends improving interactive training design, expanding participant coverage, and strengthening continuous evaluation to ensure sustainable improvements in hospital hospitality services.